Acetate-based syntrophy enhances methane production potential of ruminant feces - Liu, Jian; Sha, Yujie; Dang, Run; Zhou, Lifeng; Zhou, Meng; Tan, Yang; Wang, Jinming; Ran, Ge; Xie, Wei; Xia, Dong; Wang, Luotong; Zhao, Xingtang; et al. (Frontiers in Microbiology, 2025)
Livestock feces contribute to approximately 32% of global methane emissions. Although ruminants are generally believed to have a higher methane production potential than non-ruminants, the dominant pathways and key regulatory processes underlying methane generation in ruminants remain poorly understood, impeding effective manure management and accurate livestock emission assessments. In this study, metagenomic and carbon isotope techniques were employed to investigate methane production potential and key pathways in sheep, pig, chicken, and duck feces. Methane production potential of ruminant sheep feces was significantly higher (approximately threefold) compared to that of non-ruminants. Isotopic analysis of methane sources revealed that sheep feces primarily produce methane through the acetoclastic pathway, whereas the other three likely rely on CO2 reduction. Metagenomic analysis of methanogenic pathways further indicated that the abundance of functional genes associated with acetoclastic methanogenesis is significantly higher in sheep feces compared to the other three. Moreover, the co-occurrence network analysis highlighted a tightly coordinated, cross-species partnership between fermentative acetogenic bacteria and methanogenic archaea in the sheep fecal microbiome. Together, our findings provide insights into some key methanogenic pathways, such as acetoclastic methanogenesis, contributing to high methane production from ruminant feces.